2010
DOI: 10.1163/157180610x529636
|View full text |Cite
|
Sign up to set email alerts
|

Paying for POPs: Negotiating the Implementation of the Stockholm Convention in Developing Countries

Abstract: A key aspect of the negotiations for the 2001 Stockholm Convention on Persistent Organic Pollutants (POPs) related to provisions surrounding its financial mechanism to facilitate its implementation in developing countries. This article examines how financial aspects of the Convention were negotiated as the treaty was taking shape and how financial provisions have been implemented since the Convention's entry into force in 2004. Regarding the design of the financial mechanism, developing countries stressed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The issue of POPs begun to be addressed in the 1980s; Canada has brought it onto the international agenda [10][11][12]. In Canada, research found out and heightened the sensitivity of concerns of its northern indigenous populations.…”
Section: The Birth Of the Stockholm Conventionmentioning
confidence: 99%
“…The issue of POPs begun to be addressed in the 1980s; Canada has brought it onto the international agenda [10][11][12]. In Canada, research found out and heightened the sensitivity of concerns of its northern indigenous populations.…”
Section: The Birth Of the Stockholm Conventionmentioning
confidence: 99%
“…This is especially problematic for poorer nations that rely primarily on GEF funding that, amongst multiple projects, do not prioritize POP reduction. Additionally, the GEF does not have the capacity to assess whether funds allocated for POP removal are appropriately or effectively used (Ashton and Kohler 2010).…”
Section: Introductionmentioning
confidence: 99%